Molecular and Biochemical Characterization of Recombinant Guinea Pig Tumor Necrosis Factor-Alpha - Vijaya R. Dirisala; Amminikutty Jeevan; Lan H. Ly; David N. McMurray (Hindawi Limited, 2015)
Tumor necrosis factor alpha (TNF-α) is a cytokine which plays opposing roles in the context of infectious disease pathogenesis. TNF-α is essential for the development of a protective immune response to some pathogens, for example, Mycobacterium tuberculosis, by synergizing with other cytokines. However, exorbitant or uncontrolled TNF-α activity may also drive pathology and disease symptoms in many infectious diseases. In order to elucidate the beneficial and detrimental roles of TNF-α in tuberculosis (TB) and other diseases for which the guinea pig is the small animal model of choice, recombinant guinea pig (rgp)TNF-α has been produced using prokaryotic expression systems. However, it is unknown whether posttranslational modifications which cannot be made in the prokaryotic expression systems may be important for rgpTNF-α structure and function. Therefore, we carried out a comparative study by expressing rgpTNF-α in prokaryotic and eukaryotic expression systems and analyzed the eukaryotic-expressed rgpTNF-α for the presence of posttranslational modifications by subjecting it to NanoLC-MS/MS. We conclude that the eukaryotic-expressed rgpTNF-α lacks posttranslational modifications, and we found no significant difference in terms of the biological activity between prokaryotic- and eukaryotic-expressed rgpTNF-α. Taken together, results from our study show that a prokaryotic expression system can be used for generating large amounts of rgpTNF-α without concern for the biological integrity.